Medición del nivel de integración de los sistemas de gestión en organizaciones colombianas (2020)
Companies have devoted efforts to achieve the integration of their management systems, often without achieving this objective, generating inconspicuous results and wasting available resources. The objective of the project is to generate a valid instrument for measuring the level of integration and maturity of an Integrated Management System (IMS), applicable to Colombian organization certified in the ISO 9001, ISO 14001, OHSAS 18001 and ISO 45001 standards, in such a way that the results obtained serve as a basis for the optimization of IMS. Through descriptive-correlational quantitative research, an instrument was designed that allows 33 questions, associated with the 3 critical factors and 9 integrating variables, to capture the perception of the actors facing the IMS. A panel of experts validated this; later it was applied as pilot in a multinational and after adjustments, it was validated in three companies that fulfilled an inclusion criteria. The result is a tool that qualitatively and quantitatively evaluates the level of maturity of an IMS, the integrating variables, the state account of the critical factors that structure it and identify opportunities for improvement and strengths.